2005
DOI: 10.1007/s00213-005-2151-4
|View full text |Cite
|
Sign up to set email alerts
|

Associative and behavioral tolerance to the analgesic effects of nicotine in rats: tail-flick and paw-lick assays

Abstract: The findings suggest that contextual tolerance to drug effects is test specific, with tail-flick responses depending on cue-associative tolerance processes and hot-plate responses requiring procedures that allow the animal to practice the test response while drugged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Pharmacodynamic tolerance is represented by the classic decreased effectiveness of an opioid over time, related to upregulation of receptors. In contrast to pharmacokinetic and pharmacodynamic tolerance, learned tolerance results in a decrease in efficiency as compensated mechanisms are incorporated or learned [79]. It is illustrated by the fact that if a patient is in a setting where he or she usually consumes the drug they typically expect the drug to be less effective; whereas if the same patient takes the same amount of drug in a nonstandard setting, he or she will probably feel a greater effect.…”
Section: Opioid Tolerance and Physical Dependencementioning
confidence: 99%
“…Pharmacodynamic tolerance is represented by the classic decreased effectiveness of an opioid over time, related to upregulation of receptors. In contrast to pharmacokinetic and pharmacodynamic tolerance, learned tolerance results in a decrease in efficiency as compensated mechanisms are incorporated or learned [79]. It is illustrated by the fact that if a patient is in a setting where he or she usually consumes the drug they typically expect the drug to be less effective; whereas if the same patient takes the same amount of drug in a nonstandard setting, he or she will probably feel a greater effect.…”
Section: Opioid Tolerance and Physical Dependencementioning
confidence: 99%
“…A review of the literature fails to yield evidence of context-dependent impulsivity despite strong evidence that contextual cues can renew appetitive and avoidance responses (e.g. Bouton 2002; 2004), and facilitate both drug sensitization (Badiani, Anagnostaras, and Robinson, 1995; Badiani, Browman, and Robinson, 1995; Crombag, Badiani, Maren, and Robinson, 2000; Damianopoulos and Carey, 1992; Stewart and Vezina, 1988) and tolerance (Baker and Tiffany, 1985; Carter and Tiffany, 1996; Capeda-Benito, Davis, Reynoso, and Harriad, 2005; Siegel, Hinson, and Krank, 1978). …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, we have found that the hot-plate test is not a particularly sensitive assessment of associative tolerance to a drug's analgesic effects (Cepeda-Benito & Tiffany, 1996a). We have argued elsewhere that contextual tolerance to drug effects are test specific-that is, responses that are predominately spinally mediated (tail flick) depend on cue-associative tolerance processes, whereas responses that are predominately supraspinally mediated (hot plate) depend on behavioral tolerance processes or tolerance to the disruptive effects of a drug on instrumental performance (Cepeda-Benito et al, 2005). The 4.5-hr IDI may have produced a level of pharmacological exposure that was more similar to continuous administration regimes (Marks, Stitzel, & Collins, 1985) than to the typical chronic exposure to intermittent administrations of 1, 2, or even 3 nicotine administrations per day (Pauly et al, 1992).…”
Section: Discussionmentioning
confidence: 99%